Novel MAC Protocol and Middleware Designs for Wearable Sensor-Based Systems for Health Monitoring - Kyeong Hur; Won-Sung Sohn; Jae-Kyung Kim; YangSun Lee (International Journal of Distributed Sensor Networks)
We propose a middleware platform built on wireless USB (WUSB) over wireless body area networks (WBAN) hierarchical protocol for wearable health-monitoring systems (WHMS). The proposed middleware platform is composed of time-synchronization and localization solutions. It is executed on the basis of WUSB over WBAN protocol at each wearable sensor node comprising the WHMS. In the platform, firstly, the time-synchronization middleware is executed. After that, a WHMS host calculates the location of a receiving sensor node by using the difference between the times at which the sensor node received different WBAN beacon frames sent from the WHMS host. The WHMS host interprets the status and motion of the wearable body-sensor objects.